The Construction of Positive Social Psychology During the COVID-19 Pandemic: Exploring the Relationship Between Social Support and Peace of Mind Through a Three-Wave Longitudinal Cross-Lag Study - Xi, Yiheng; Zhou, Li; Wang, Ying (Frontiers in Psychology, 2021)
The ongoing Covid-19 pandemic has sparked a major global crisis that has infected public social mentality. Drawing on the concept of peace of mind (PoM), a culture-specific positive emotion construct developed in Chinese cultural context, the present study explored the ways to build a positive public social mentality in the time of the pandemic. PoM is indicative of a calm and stable emotional state marked by self-control and spiritual cultivation and is believed to align with the perceptions of subjective well-being in Chinese or eastern cultures (Lee et al., 2013). A three-wave cross-lag study using online questionnaire survey was conducted in 107 employees in Chinese enterprises during the pandemic. The research findings suggest that social support had a significant positive time-cross effect on later PoM, i.e., social support-T1 had a significant predictive effect on PoM-T2 (β = 0.16, SE = 0.09, p < 0.05) and social support-T2 had a significant predictive effect on PoM-T3 (β = 0.38, SE = 0.19, p < 0.05), whereas PoM failed to show a positive time-cross effect on later social support, i.e., the predictive effects of PoM-T1 on social support-T2 (β = 0.04, SE = 0.07, p > 0.05) and of PoM-T2 on social support-T3 (β = 0.13, SE = 0.09, p > 0.05) were not significant. This study provided a dynamic picture of the construction of public social mentality in the time of public health emergencies, and also contributed to the research on PoM antecedents.